The global public health significance of Plasmodium vivax. - Battle, K; Gething, P; Elyazar, I; Moyes, C; Sinka, M; Howes, R; Guerra, C; Price, R; Baird, J; Hay, S (2012)
Plasmodium vivax occurs globally and thrives in both temperate and tropical climates. Here, we review the evidence of the biological limits of its contemporary distribution and the global population at risk (PAR) of the disease within endemic countries. We also review the most recent evidence for the endemic level of transmission within its range and discuss the implications for burden of disease assessments. Finally, the evidence-base for defining the contemporary distribution and PAR of P. vivax are discussed alongside a description of the vectors of human malaria within the limits of risk. This information along with recent data documenting the severe morbid and fatal consequences of P. vivax infection indicates that the public health significance of P. vivax is likely to have been seriously underestimated.